A positive surgical margin does not affect survival - Rassweiler, Jens; Gözen, Ali Serdar (Nature reviews. Urology, 2013)
The incidence and consequences of positive surgical margins after partial nephrectomy are important issues in the management of localized renal cell carcinoma. A recent population-based study demonstrates a slightly higher rate of positive margins than previously reported in monocentric studies. However, margin status had no impact on overall or disease-specific survival.
Gesehen am 16.12.2021